Pengaruh Promosi, Persepsi Harga dan Citra Merek Terhadap Keputusan Pembelian di Blue Jasmine Restaurant - Ali Agung Komara; Chatarina Yunita (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aims to determine the effect of promotion, perceived price, and brand image on purchasing decisions at Blue Jasmine Restaurant. This research uses survey-based quantitative research by means of a purposive sample of 100 respondents. This study uses data collected directly from respondents which include their perceptions of the promotion aspect, perceived price, and brand image. Based on the results of this study, promotion does not have a significant effect on purchasing decisions, perceived price has a significant influence, and brand image also has a significant effect on purchasing decisions. Finally, it shows that price perception and brand image together have a significant effect on purchasing decisions, while promotions have no effect on purchasing decisions at Blue Jasmine Restaurant.